Relationship Between The Body Mass Index With The Degree Of Asthma In Children 1-12 Years Of Age At Children's Clinic Wangaya Hospital Denpasar. - I Gusti Ayu Sikha Permata A.S. (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Asthma is a disease caused by a respiratory condition that is very sensitive to various stimuli, both from within and outside the body. As a result of this excessive sensitivity of airway narrowing occurs as a whole. Asthma in children can be classified into several groups, namely rare episodic asthma, frequent episodic asthma and persistent asthma. Asthma and obesity is the body currently more common in children than a few decades ago. This study aims to analyze the Relationship Between The Body Mass Index With The Degree Of Asthma In Children 1-12 Years Of Age At Children's Clinic Wangaya Hospital Denpasar. This study includes the type of descriptive correlational study using cross sectional design. Sample consisted of 28 patients with asthma who came to the Children's Clinic Wangaya Hospital taken using non probability sampling technique that is kind of Consecutive Sampling. The data was collected by interviews based on questionnaires to the parents of patients and figure BMI patients. The results with the Spearman rank correlation test p value = 0.000 obtained, the value of ? = 0.05, p <0.05 (5%) and compute r = 0.709> r table = 0.377, which means there is a significant Relationship Between The Body Mass Index With The Degree Of Asthma In Children 1-12 Years Of Age At Children's Clinic Wangaya Hospital Denpasar. Positive values ??indicate a correlation coefficient of the direct relationship between two variables. In other words, the higher the child's body mass index is the degree of childhood asthma is also higher.